(untitled) (Bulletin KNOB, 2006)
With the publication of the twelfth and last part in July 2006 the series ‘Monumenten in Nederland’ was completed after more than ten years. For the first time in a long while a general survey has thus become available covering the entire Netherlands, presenting a coherent overview of the cultural-historically most valuable structures and objects. Although it comprises fewer volumes, but is of a larger format and contains more illustrations, the series can measure up to ‘The Buildings of England’ of Nicolaus Pevsner, published between 1951 and 1974. In ‘Monumenten in Nederland’ not only protected, but also - if interesting - not (yet) protected buildings are dealt with, not just as such, but also in their historical, architectonic, and building-historical context. As regards the national coverage a great extent of balance was aimed at in the series, so that not only the most important but, on the contrary, all the relevant buildings in every corner of the country are brought up. Thus it has become a Cultural Topography. In the relatively short - by standards of historic building surveys period of ten years it proved to be possible to look at the entire stock of historic buildings with a coherent vision as regards contents. Consequently, the major historical parameters: place, periodization, style and type have been systematically and consistently dealt with in the whole series. Within the framework of a growing building-historical insight compared to the existing literature some slight corrections were occasionally made. Likewise, materials and constructions were dealt with better. Besides, ample attention has been paid to cultural connections, both of church and parsonage, factory and porter’s house, but also in a wider context, such as the branching off from a town hall into law, records and police functions, each in a separate building. Behind spatial developments there often are energetic persons who erected country estates, factory complexes or areas under development with the accompanying buildings. This aspect also received much attention. Due to the consistency in concise description referred to, it became possible to develop a relative cultural measure reflecting a relative order of merit of cultural-historically important towns and villages better than just on the basis of a number of protected monuments. In recent preservation of monuments and historic buildings attention shifted from the object towards the spatial development. In the meantime this balance threatens to tip towards an excess of cultural planology, whereby not just the individual building but also the historical aspect is somewhat lost sight of. With a profound attention for the spatial aspects ‘Monumenten in Nederland’ has focused on the large group of cultural-historically important buildings and objects again and thus it is a ’benchmark’ of monuments and historic buildings in the Netherlands on the transition from the 20th to the 21st century.